Strategic Planning and Analysis for Commercial Banking: An Analysis based a Commercial Bank Operating in Srilanka - Sanjeepan, Navaretnarajah (Journal of Asian Business Strategy, 2017)
This article has been consisted on the basis of an ample interpretation of banking sector strategic planning that, along with the instruments and techniques from which it stems, constitutes the essential condition to operate in competitive markets. The concept of planning is examined in its stages, its importance and the benefits for the banking sector in implementing scheduling. The strategic plan model proposed here for the banking sector is examined in detail through the steps towards implementing a plan that leading to the business improvement.